2017
DOI: 10.1590/1678-77572016-0173
|View full text |Cite
|
Sign up to set email alerts
|

Short-term transcutaneous electrical nerve stimulation reduces pain and improves the masticatory muscle activity in temporomandibular disorder patients: a randomized controlled trial

Abstract: Studies to assess the effects of therapies on pain and masticatory muscle function are scarce. Objective To investigate the short-term effect of transcutaneous electrical nerve stimulation (TENS) by examining pain intensity, pressure pain threshold (PPT) and electromyography (EMG) activity in patients with temporomandibular disorder (TMD).Material and Methods Forty patients with myofascial TMD were enrolled in this randomized placebo-controlled trial and were divided into two groups: active (n=20) and placebo … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
61
0
10

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 59 publications
(71 citation statements)
references
References 26 publications
(35 reference statements)
0
61
0
10
Order By: Relevance
“…Risk of bias was very heterogeneous among studies. Using Cochrane Collaboration's tool, nine studies were classified as low risk of bias, 13 as unclear and 20 as high risk of bias . The higher risk of bias was reporting bias.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Risk of bias was very heterogeneous among studies. Using Cochrane Collaboration's tool, nine studies were classified as low risk of bias, 13 as unclear and 20 as high risk of bias . The higher risk of bias was reporting bias.…”
Section: Resultsmentioning
confidence: 99%
“…Out of the 42 RCTs, sample size ranged from 13 20 to 99 21 with a total of 1657 patients, mostly women, that is from 47 22 up to 100% 23-31 of the sample. Studies were conducted in Brazil, 23,26,28,30,[32][33][34][35][36][37][38][39] Canada, 24,40 China, 41 Croatia, 20 Denmark, [42][43][44] India, 45 Iran, 29,46 Italy, 21 Korea, 22 Poland, 47 Spain, 48 Sweden, [49][50][51] Thailand, 52 the Netherlands, 53 Turkey, [54][55][56] United Kingdom 57 and United States of America (USA). 25,27,31,[58][59][60][61] All studies were published in the English language.…”
Section: Study Characteristics and Results Of Individual Studiesmentioning
confidence: 99%
See 1 more Smart Citation
“…ES as a new and developing treatment has been applied in clinical settings for many years. Ferreira et al [19] found that the temporomandibular disorder treatment process, ES mitigated pain and improved masticatory muscle activity efficiently, without drugs or the need for invasive procedures. Rajfur et al [10] found that electrical therapy was effective in treating chronic low back pain.…”
Section: Discussionmentioning
confidence: 99%
“…Ferreira.et al [15,28] proved that the therapeutic effects of TENS are superior to those of the placebo. In recent years, several RCTs compared LLLT with TENS for treating patients suffering from TMD [10,12,14,29].…”
Section: Introductionmentioning
confidence: 99%